Charm and Bottom hadron production with a coalescence plus fragmentation hadronization approach: AA system size scan down to pp collisions - Plumari Salvatore; Minissale Vincenzo; Greco Vincenzo (EPJ Web of Conferences)
Heavy baryon production in pp, pA, and AA collisions at RHIC and LHC energies provides new challenges to the theoretical understanding of heavy-quark hadronization. In recent years, a hybrid coalescence-plusfragmentation model has successfully predicted the large baryon/meson ratio observed in AA and pp collisions. This approach also predicts an enhancement of Ξc and Ωc production in pp collisions that is in agreement with the recent ALICE data. In this paper, we provide predictions for bottom hadrons in PbPb and pp collisions at LHC energies. The comparison between charm and bottom hadron production offers new insights into both the hadronization mechanisms. Finally, the extension of the model to multi-charmed baryons like Ξcc and Ωccc has shown that multi-charmed baryon yields, especially Ωccc, are sensitive to the thermalization of charm quarks, offering insights into hadronization and quark equilibration dynamics across different systems.